Organising the Firm - Mäntysaari, Petri. author. aut Link
VII, 167 p.
Keywords: Commercial law, corporate governance and corporate law deal with the organisation of firms. This book proposes a coordinated answer to three problems - the absence of theories of commercial law, the failure of existing theories of corporate governance to explain the actual behaviour of firms, and the failings of existing theories to explain the contents of corporate law. All three areas can be studied from the perspective of the firm. After analysing previous theories, the book proposes a theory of commercial law, defines the law of corporate governance as an area of law, and proposes a new theory of corporate law. In addition, the book shows how firms can increase sustainability by choosing self-enforcing governance models and governance models that foster innovation.